Neoantigens: new hope for cancer therapy - Yitong Hu; Tengda Zhou; Ping Cai; Ping Cai; Zihao He (Frontiers in Oncology)
As research into tumour immunotherapy continues to accelerate, new frontiers are being revealed in the field of cancer treatment. A significant focus has been drawn to neoantigen-based personalised tumour vaccines, a pioneering immunotherapy. This approach involves the use of genetic mutations that are unique to tumor cells to custom-design personalized tumor vaccines. These vaccines elicit an immune response that is specifically directed at targeting and eliminating cancer cells. The incorporation of neoantigens, arising from mutations within tumor cells, confers a distinct advantage to personalized tumor vaccines in terms of precision and the mitigation of adverse effects. However, the intricate pathways from antigen presentation to the activation of tumor immunogenicity remain to be elucidated. This paper primarily delves into the origins and characteristics of neoantigens, and also neoantigen prediction, highlights existing screening methods, and addresses the limitations of current approaches. It is hoped that this review will act as a catalyst, accelerating the understanding of relevant knowledge and illuminating research hotspots for scientists poised to venture into neoantigen research.